1996
DOI: 10.1269/jrr.37.1
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Protein Found After X-Irradiation in Human T Cell Leukemia.

Abstract: An X-ray-induced protein in human T cell leukemia MOLT-4 cells is described. It was detected 4 hrs after irradiation by two dimensional gel electrophoresis and silver staining. The location is 41 kDa in the mass and 4.0 of pI. Its spots were collected from the gels and microsequenced. The protein was identified from its partial sequences as a set gene product, whose gene translocation previously was found in a case of acute undifferentiated leukemia. Polyclonal rabbit antibodies stained two spots, the 41 kDa (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…p41 is induced after IR through cleavage of p42/SETb and appears to be a specific catalytic product of caspase-7 and a marker of apoptosis. 4,5 Caspases are a family of aspartate-specific cysteine proteases activated during apoptosis, and are normally present in cells as proenzymes that require limited proteolysis for the activation of enzymatic activity. Activated caspases precipitate the irreversible commitment of the cell to apoptotic death by cleaving a number of substrates, many of which have been identified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…p41 is induced after IR through cleavage of p42/SETb and appears to be a specific catalytic product of caspase-7 and a marker of apoptosis. 4,5 Caspases are a family of aspartate-specific cysteine proteases activated during apoptosis, and are normally present in cells as proenzymes that require limited proteolysis for the activation of enzymatic activity. Activated caspases precipitate the irreversible commitment of the cell to apoptotic death by cleaving a number of substrates, many of which have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…13 In our research, vanadate was originally found to be an inhibitor of p41 induction in irradiated MOLT-4 cells, although this induction is mediated by caspase-7. 4,5 The objective of this study was to clarify the effect of vanadate, and we speculated that the inhibitory effect of vanadate on the cleavage of p42/SETb to p41 would be due to suppression of either the activation or the activity of caspases. Therefore, we investigated the effect of vanadate on caspases and related apoptotic processes.…”
Section: Introductionmentioning
confidence: 99%
“…The present study dealt with the newly found protein, p41, a radiation-induced protein appeared dose and time dependently and detected by 2-D PAGE and silver staining during the rapid cell death (4). Immunoblotting analysis by a polyclonal antibody, AM-1, raised against a synthetic partial peptide of p41, showed two spots, p41 and an additional acidic 42-kDa protein, p42, unexpectedly.…”
mentioning
confidence: 90%
“…A rabbit polyclonal antibody, AM-1, against common region of p41 and p42 was raised as described previously (4). YM-CS.1, a rabbit polyclonal antibody against the catalytic subunit of DNA-PK (DNA-PKcs) was described previously (2).…”
Section: Measurement Of Viabilitymentioning
confidence: 99%
“…2,3,[7][8][9] We have been involved in studies to clarify mechanisms of tumor metastasis and cellular radiation response. 2,3,[10][11][12] In our recent studies, MUC1 in tumor cells was found to be increased by a novel soluble factor present in normal colon tissue culture conditioned medium (NCCM) [13][14][15][16] or by other agents such as 5-FU. 17) However, the effect of radiation on MUC1 has not been clarified, so we have been investigating if MUC1 expression in tumor cells could be modified by irradiation and be a biomarker for irradiation effect, and also if modified MUC1 expression is relevant to metastatic behavior.…”
mentioning
confidence: 99%